The Impact Analysis Of Current Human Resource Management Issues Toward Motivation Function: Outsourcing, Mergers-Acquisitions, And Contractual Workers - Rony Setiawan; Henky Lisan Suwarno (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2009)
Three main issues which growing in Indonesia in the field of human resource management is: outsourcing, mergers-acquisitions, and contractual workers. These issues effect on job insecurity among workers in company. Job insecurity can decrease workers performance directly and company performance indirectly. Authors describe the practice of those issues in several companies in service industries. Authors give recommendation that organization should manage those issues by concern on motivation function through extrinsic and intrinsic motivation.